2013
DOI: 10.1007/s10735-013-9552-1
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 expression and regulation in the mouse uterus during embryo implantation

Abstract: The aim of this study was to investigate the spatiotemporal expression and regulation of GRP78 in the mouse uterus during the peri-implantation period. The GRP78 protein was mainly detected in the luminal and glandular epithelia on days 1-4 of pregnancy. On day 5 of pregnancy, the GRP78 protein was more highly observed around the implanted embryo at the implantation site. There was no detectable GRP78 protein signal on day 5 of pseudopregnancy. GRP78 mRNA and protein levels gradually increased on days 6-8 of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…However, regardless of whether ERS is initiated under physiological conditions or not, previous studies have suggested that, compared with the control, the expression of Grp78 in mouse decidual uterus does not change significantly (Simmons and Kennedy 2000), suggesting that ERS might not be involved in decidualization. In contrast, our previous studies have suggested that Grp78 is remarkably upregulated in pregnant mouse uteri at day 5 (embryo implantation has occurred) and days 6-8 (decidualization; Lin et al 2014). These results indicate that ERS might be involved in decidualization.…”
Section: Involvement Of Ers Response In Embryo Implantation and Decidcontrasting
confidence: 69%
“…However, regardless of whether ERS is initiated under physiological conditions or not, previous studies have suggested that, compared with the control, the expression of Grp78 in mouse decidual uterus does not change significantly (Simmons and Kennedy 2000), suggesting that ERS might not be involved in decidualization. In contrast, our previous studies have suggested that Grp78 is remarkably upregulated in pregnant mouse uteri at day 5 (embryo implantation has occurred) and days 6-8 (decidualization; Lin et al 2014). These results indicate that ERS might be involved in decidualization.…”
Section: Involvement Of Ers Response In Embryo Implantation and Decidcontrasting
confidence: 69%
“…We used experimental mouse models of normal pregnant mice and OVX mice, according to previous studies (Lin et al, ). The model of normal pregnancy was used to investigate the spatiotemporal expression of RGS2 in the uterus during implantation.…”
Section: Methodsmentioning
confidence: 99%
“…However, examining the direct role of RGS2 in embryonic invasion, in decidualization of ESCs, and in identifying which G-protein-coupled signaling pathways are involved in the interactions between embryo and uterus during implantation requires further investigation. We used experimental mouse models of normal pregnant mice and OVX mice, according to previous studies (Lin et al, 2014). The model of normal pregnancy was used to investigate the spatio-temporal expression of RGS2 in the uterus during implantation.…”
mentioning
confidence: 99%
“…Many ER-stress-related gene expressions change during embryo implantation, suggesting that ER stress may be an essential step in embryo implantation. On day 5 of pregnancy in mice, the GRP78 protein was more highly observed around the implanted embryo at the implantation site, and we understand that the change of GRP78 expression means the occurrence of ER stress [87]. On the other hand, calcium homeostasis can cause ER stress, and ER stress and UPR regulate calcium homeostasis [88].…”
Section: Endoplasmic Reticulum Stress and Decidualizationmentioning
confidence: 94%